A survey of tasks performed by School Library Media Center personnel in selected private schools in Metro Manila - Buenrostro, Joel S. (1996)
This study aims to identify the tasks performed by a variety of personnel in exemplary school library media center programs in Metro Manila. The descriptive survey method was used. The subjects were the SLMC professional and support staff of four selected private schools in Metro Manila, namely : Assumption College, Ateneo de Manila University, Claret School and Xavier School. A questionnaire patterned after the task analysis survey instrument developed for the School Library Manpower Project by Research Division of the National Education Association was used to gather data.